Routing-Gi: routing technique to enhance energy efficiency in WSNs. (2017) - Alami, Hassan El; Najid, Abdellah
Wireless sensors networks (WSNs) are realised as one of the most promising networking types that bridge the gap between the cyber and the things. Designing of routing protocols for WSNs is a challenging issue since sensors are mostly limited in energy and data processing. In this paper, we present a new routing technique for hierarchical routing protocols to enhance energy efficiency in WSNs, namely Routing-Gi . This technique divides network area into the inner grid and clustered grids. In an inner grid, the nodes transmit directly data to the base station (BS), whereas, in clustered grid, the nodes are organised into micro-grids and thus each node transmits data to the BS through it respective cluster head. in this case, the micro-grids help to avoid unbalanced energy consumption in WSNs. Thus, the workload is evenly distributed on nodes causing the efficient energy of network to enhance. The simulation results prove the effectiveness of our technique.